2021
DOI: 10.1093/qje/qjab019
|View full text |Cite
|
Sign up to set email alerts
|

Strict Id Laws Don’t Stop Voters: Evidence from a U.S. Nationwide Panel, 2008–2018

Abstract: U.S. states increasingly require identification to vote – an ostensive attempt to deter fraud that prompts complaints of selective disenfranchisement. Using a difference-in-differences design on a 1.6-billion-observations panel dataset, 2008–2018, we find that the laws have no negative effect on registration or turnout, overall or for any group defined by race, gender, age, or party affiliation. These results hold through a large number of specifications. Our most demanding specification controls for state, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 94 publications
3
22
0
Order By: Relevance
“…which is about 0.116 percent of the 2016 primary electorate in North Carolina. This is consistent with Cantoni and Pons (2019), which finds small effects of voter ID laws on overall turnout using a nationwide voter file panel. Even in a large nationwide panel researchers lack the power to detect this sized effect.…”
Section: Characterizing the Overall Effect Of The Id Lawsupporting
confidence: 87%
See 1 more Smart Citation
“…which is about 0.116 percent of the 2016 primary electorate in North Carolina. This is consistent with Cantoni and Pons (2019), which finds small effects of voter ID laws on overall turnout using a nationwide voter file panel. Even in a large nationwide panel researchers lack the power to detect this sized effect.…”
Section: Characterizing the Overall Effect Of The Id Lawsupporting
confidence: 87%
“…To assess the effects of voter ID laws, scholars compare turnout in states that have voter ID requirements with those that do not, using either aggregate state-level turnout or self-reported turnout data (Erikson and Minnite, 2009). Some designs have found no effect on turnout (Mycoff et al, 2009;Hood and Bullock, 2012;Highton, 2017;Cantoni and Pons, 2019), while others have found negative effects on turnout (Alvarez et al, 2008;Barreto et al, 2009;Alvarez et al, 2011;Hajnal et al, 2017). Yet, if the effect of voter ID laws persists, then states that are classified as "control" states after a law is repealed will still have voters affected by the law being in place; and as a result, the most common research designs will be biased toward finding no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Research around the impact of voter identification laws on turnout is mixed (Erikson and Minnite, 2009; Hershey, 2009). Several studies conclude that the impact of voter ID laws on turnout is negligible (Erikson and Minnite, 2009; Mycoff et al ., 2009; Grimmer et al ., 2018; Cantoni and Pons, 2021). Others find that the strictest laws have a depressive effect, but do not find differences among racial and ethnic groups (Hood and Bullock, 2012; Hood and Buchanan, 2020).…”
Section: Relevant Literaturementioning
confidence: 99%
“…16 A working paper found that new laws to require voter identification between 2008 and 2018 failed to depress registration or turnout including among voters of color. Part of the reason is countermobilizationincreased contacts by the candidate organizations and Democratic Party (Cantoni and Pons 2021).…”
Section: State Lawsmentioning
confidence: 99%